Understanding the stagnation and burn of implosions on NIF. (March 2016) - Kilkenny, J D; Caggiano, J A; Hatarik, R; Knauer, J P; Sayre, D B; Spears, B K; Weber, S V; Yeamans, C B; Cerjan, C J; Divol, L; Eckart, M J; Glebov, V Yu; et al.
Abstract: An improved the set of nuclear diagnostics on NIF measures the properties of the stagnation plasma of implosions, including the drift velocity, areal density (ρr) anisotropy and carbon ρr of the compressed core. Two types of deuterium-tritium (DT) gas filled targets are imploded by shaped x-ray pulses, producing stagnated and burning DT cores of radial convergence (Cr ) ∼ 5 or ∼20. Comparison with two-dimensional modeling with inner and outer surface mix shows good agreement with nuclear measurements.